Kernel Causality Among Teacher Self-Efficacy, Job Satisfaction, School Climate, and Workplace Well-Being and Stress in TALIS - Zhang, Xue; Zhao, Chunyang; Xu, Yuqiao; Liu, Shanhuai; Wu, Zhihui (Frontiers in Psychology, 2021)
Teacher plays an important role in the educational system. Teacher self-efficacy, job satisfaction, school climate, as well as workplace well-being and stress are four individual characteristics shown to be associated with tendency to turnover. In this article, data from TALIS 2018 teacher questionnaire are analyzed, with the goal to understand the interplay amongst these four individual characteristics. The main purposes of this study are to (1) measure extreme response style for each scale using unidimensional nominal response models, and (2) investigate the kernel causal paths among teacher self-efficacy, job satisfaction, school climate and workplace well-being and stress in the TALIS-PISA linked countries/economies. Our findings support the existence of extreme response style, the rational non-normal distribution assumption of latent traits, and the feasibility of kernel causal inference in educational sector. Results of the present study inform the development of future correlational research and policy making in education.